PERBEDAAN FORTIFIKASI BESI (FeSO4 - NaFeEDTA) TERHADAP KADAR BESI, pH DAN TINGKAT KESUKAAN PADA SUSU FERMENTASI SINBIOTIK (L. plantarum Dad. 13 - FOS) SELAMA MASA SIMPAN - , KURNIA WIDYASTUTI; , Siti Helmyati, DCN, M.Kes ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background : Food fortification are cost-effectives solutions, long-term effect, and can be used as intervention for tackling anemia. Source of iron that usually used as fortificant is FeSO4 because of its low price. NaFeEDTA has specific characteristic and many benefits. Fermented milk is one of the potential food carrier for iron fortification. The addition of local probiotic, Lactobacillus plantarum Dad 13 which have so many benefits in health into fermented milk is to enhance the growth of commensal gut bacteria so that it can minimize the negative effect of iron administration (diarrhea). The used of prebiotic fructooligosaccharide (FOS) is to give synbiotic effect which will help increase the life time of probiotic by giving specific substrate for fermentation. Objectives : To know the effect of iron fortification of synbiotic fermented milk with local probiotic L. plantarum Dad 13 and prebiotic Fructooligosacharide on iron content and pH during storage periode, and level of preference by semi-trained panelists. Methods : This study was experimental research. Synbiotic fermented milk were divided into three groups: 1) control/no fortification/Co, 2) fortified with FeSO4/FeS, and 3) NaFeEDTA/ NaF, each of 50 ppm iron. During storage (d-1 and d-7 after fermentation), iron content was measured by using dry ashing method then followed by AAS (atomic absorption spectrophotometry) and pH value by using digital pH-meter. Preference test in taste, flavour, color and texture was carried out by 33 semi-trained panelists. Result : After one week of storage, there was a significant difference (p= 0,00) of iron content among three groups whereas FeS had the highest iron content compared with NaF and Co: 28.90 ppm, 16.46 ppm, and 1.37 ppm, respectively. pH value among three groups did not differ significantly (p=0,095). There was a significant difference of level preference in flavour (p=0,036) and taste (p=0,02) but no different in color (p = 0,137) and texture (p=0,779) among three groups. Overall NaF had the highest total score in the level of preference. Conclusion : Seven days storage periode after fermentation, there was a significant differences of iron content among three groups which FeSO4 milk had the highest iron content but no significant differences of pH value among three groups. There was a significant difference of level preference in flavour and taste but no different in color and texture among three groups.